Comparative Evaluation on Supervised Learning Based Age Estimation - Micheal, A. Annie; Geetha, P; Saranya, A (International Journal of Computer Sciences and Engineering, 2025)
Facial age estimation has got more consideration in the area of computer vision for the past few years. Age estimation is a troublesome task since the distinction between facial pictures with age variations is difficult. In this work, we analyze the problem of age prediction by means of SVR Model and deep learning technique. This paper attempts to find out the efficiency of SVR and Convolution neural network (CNN) on age estimation. Local features such as wrinkles and texture are extracted using Gabor filter, Local Binary Pattern (LBP) and Local Phase Quantization (LPQ). The three features are combined together and the dimension of the feature vector is reduced using Principle Component Analysis. Support Vector Regression (SVR) is utilized to predict the age of an individual. In CNN, the datasets are fine-tuned utilizing the pre-trained VGG-16 model which can group pictures into 1000 categories. The experimental results on the IMDB-WIKI dataset, the ICCV datasets and MORPH 2 dataset shows that CNN outperforms the local feature based SVR model in predicting the age